UK food and nutrition security during and after the COVID‐19 pandemic. Issue 1 (19th February 2021) - Rivington, M.; King, R.; Duckett, D.; Iannetta, P.; Benton, T. G.; Burgess, P.J.; Hawes, C.; Wellesley, L.; Polhill, J. G.; Aitkenhead, M.; Lozada‐Ellison, L.‐M.; Begg, G.; et al.
Abstract: The COVID‐19 pandemic is a major shock to society in terms of health and economy that is affecting both UK and global food and nutrition security. It is adding to the 'perfect storm' of threats to society from climate change, biodiversity loss and ecosystem degradation, at a time of considerable change, rising nationalism and breakdown in international collaboration. In the UK, the situation is further complicated due to Brexit. The UK COVID‐19 F ood and N utrition S ecurity project, lasting one year, is funded by the Economic and Social Research Council and is assessing the ongoing impact of COVID‐19 on the four pillars of food and nutrition security: access, availability, utilisation and stability. It examines the food system, how it is responding, and potential knock on effects on the UK's food and nutrition security, both in terms of the cascading risks from the pandemic and other threats. The study provides an opportunity to place the initial lessons being learnt from the on‐going responses to the pandemic in respect of food and nutrition security in the context of other long‐term challenges such as climate change and biodiversity loss.